The Evolution of China’s Sports Industry Policies, Stage Characteristics and Development Trends - Kang, Lu (Quality in Sport, 2025)
The formulation of industrial policies has been closely intertwined with the development trajectory of the sports industry. A systematic examination of policy evolution can enhance our comprehension of the industry’’s developmental processes and facilitate predictions regarding future trajectories. This study conducts a longitudinal analysis of 186 policy documents promulgated between 1978 and 2022, utilizing social network analysis, thematic keyword analysis and semantic network analysis. Our periodization framework identifies four distinct evolutionary phases: germination period(1978-1991), initial formation period(1992-2000), stable development period(2001-2013), and strategic cceleration period(2014-2022), with the general characteristics of gradually increasing the number of policies, expanding the scope of policy subjects and enhancing the effectiveness of policies. The analysis reveals three cardinal evolutionary patterns: (1) Governance transition from unilateral departmental oversight to cross-ministerial collaborative networks; (2) Paradigm shift from restrictive administration to developmental incentivization; (3) Discursive transformation from conceptual ambiguity to operational precision. The four stages demonstrate distinct policy priorities characterized by operational pluralism in foundational development, regulatory frameworks for market formation, service-oriented governance mechanisms, and whole-industry-chain optimization strategies. These findings illuminate China’s unique pathway in cultivating sports industrialization through iterative policy experimentation, offering theoretical insights into transitional economies’’ industrial policy formulation and practical implications for global sports governance models.